2021
DOI: 10.3390/vaccines9050451
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of an Aeromonas hydrophila Multi-Gene Deletion Strain and Evaluation of Its Potential as a Live-Attenuated Vaccine in Grass Carp

Abstract: Aeromonas hydrophila is an important pathogen that causes motile Aeromonas septicemia (MAS) in the aquaculture industry. Aerolysin, hemolysin, serine protease and enterotoxins are considered to be the major virulence factors of A. hydrophila. In this study, we constructed a five-gene (aerA, hly, ahp, alt and ast) deletion mutant strain (named Aeromonas hydrophila five-gene deletion strain, AHFGDS) to observe the biological characteristics and detect its potential as a live-attenuated vaccine candidate. AHFGDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Bacteriological studies carried out during the experiment showed that on the 5th day there were no significant differences between the fish of the experimental and control groups (Table 1). The control reisolation on the 10th day after infection showed that the contamination of the parenchymal organs of the fish of the control group remained at a high level (1.2x10 7 -8.4x10 7 ), while in the experimental group a pronounced decrease in contamination was noted (2.0x10 5 -5.2x10 6 ) or even absence of increase compared to the first reisolation (1.9x10 7 -3.5x10 7 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Bacteriological studies carried out during the experiment showed that on the 5th day there were no significant differences between the fish of the experimental and control groups (Table 1). The control reisolation on the 10th day after infection showed that the contamination of the parenchymal organs of the fish of the control group remained at a high level (1.2x10 7 -8.4x10 7 ), while in the experimental group a pronounced decrease in contamination was noted (2.0x10 5 -5.2x10 6 ) or even absence of increase compared to the first reisolation (1.9x10 7 -3.5x10 7 ).…”
Section: Resultsmentioning
confidence: 90%
“…Both in natural ecosystems and in aquaculture conditions, fish are often exposed to mass infections with aeromonosis, which can cause significant economic damage to fish farms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A catfish-derived vAh strain selected for resistance to two antibiotics demonstrated significant protection in channel catfish and Nile tilapia when IP-injected, resulting in 86–100% protection relative to naïve fish [ 49 ]. Attenuated vaccines to protect fish from vAh were generated by selecting for antibiotic resistance [ 50 ] or generating attenuated vAh via multiple gene deletions [ 51 ]. An attenuated vAh strain resistant to both novobiocin and rifampicin was used to vaccinate channel catfish by IP, resulting in 100% protection against the parent vAh strain with evidence for a strong antibody-mediated response and induction of Na(+)/K(+) ATPase α subunit, hepcidin, interleukin-1β, and lysozyme c within the anterior kidney in vaccinated fish relative to naïve fish [ 50 ].…”
Section: Bacterial Pathogens Commonly Observed In Catfish Culturementioning
confidence: 99%
“…The mutant strain yielded an RPS of 70 or 75% when fish were vaccinated by immersion and subsequently challenged by two different vAh strains. An RPS of 75 or 85% was obtained when fish were vaccinated by intracelomic injection and challenged by vAh strains [ 51 ].…”
Section: Bacterial Pathogens Commonly Observed In Catfish Culturementioning
confidence: 99%
“…When water pollution, high stocking density, and improper breeding operations increase the risk of sepsis outbreaks (Azzam-Sayuti et al 2021 ). The disease can cause swelling, necrosis, ulceration, and hemorrhagic septicemia in fish tissues, and the incidence rate is fast, and the mortality rate is also very high, causing huge economic losses to fish farmers (Li et al 2021 ). Therefore, the prevention and control of such diseases is the focus of prevention and control in fish aquaculture.…”
Section: Introductionmentioning
confidence: 99%